The Role of Detraining in Tendon Mechanobiology - Frizziero, Antonio; Salamanna, Francesca; Della Bella, Elena; Vittadini, Filippo; Gasparre, Giuseppe; Nicoli Aldini, Nicolò; Masiero, Stefano; Fini, Milena (Frontiers in Aging Neuroscience, 2016)
Introduction: Several conditions such as training, aging, estrogen deficiency and drugs could affect the biological and anatomo-physiological characteristics of the tendon. Additionally, recent preclinical and clinical studies examined the effect of detraining on tendon, showing alterations in its structure and morphology and in tenocyte mechanobiology. However, there is a paucity of data examining the impact that cessation of training may have on tendon. In practice, we do not fully understand how tendons respond to a period of training followed by sudden detraining. Therefore, within this review, we summarize the studies where tendon detraining was examined. Materials and methods: A descriptive systematic literature review was conducted by searching three databases (PubMed, Scopus and Web of Knowledge) on tendon detraining. Original articles in English from 2000 to 2015 were included. In addition, the search was extended to the reference lists of the selected articles. A public reference manager (“www.mendeley.com”) was used to delete duplicate articles. Results: An initial literature search yielded 134 references (www.pubmed.org: 53; www.scopus.com: 11; www.webofknowledge.com: 70). 15 publications were extracted based on the title for further analysis by two independent reviewers. Abstracts and whole articles were then reviewed to detect if they met inclusion criteria. Conclusions: The revised literature comprised 4 clinical studies and an in vitro and three in vivo reports. Overall, the results showed that tendon structure and properties after detraining are compromised, with an alteration in the tissue structural organization and mechanical properties. Clinical studies usually showed a lesser extent of tendon alterations, probably because preclinical studies permit an in-depth evaluation of tendon modifications, which is hard to perform in human subjects. In conclusion, after a period of sudden detraining (e.g. after an injury), physical activity should be restarted with caution, following an appropriate rehabilitation program. However, further research should be performed to fully understand the effect of sudden detraining on tendons.